PERANCANGAN DAN ANALISIS ALAT MICROBUBBLE GENERATOR (MBG) UNTUK AERASI KOLAM IKAN TIPE NOZZEL VENTURI - Denis Abdur Rofik (Gorontalo Journal of Infrastructure and Science Engineering, 2020)
This study aims to apply a kind of aeration in a fish pond called Microbubble Generator (MBG) to the cultivation of fish. Microbubble Generator (MBG) carried on based on the principle of a tube venturi in which water circulates through a channel narrows so that air that is sucked into a device and driven by water flowing to make micro is the size of bubbles. Microbubble Generator (MBG) Tested in fish breeding research center Subang (BRPI), the results highlight the potential promised Microbubble Generator (MBG) as aeration affordable to applied in cultivation. Notwithstanding the oxygen dissolved do not differ significantly with aeration conventional, Microbubble Generator (MBG) shows degradation faster than organic content in water and induced a faster growth. Nozzle venturi is made with a different form between the input and output. The input nozzle venturi semicircular 18 mm in diameter than the 3mm in diameter and output, as for the output conical 8mm in diameter and output in the 14mm and the diameter of flow water use semi jet pump. The result of testing Microbubble Generator (MBG) where the initial conditions oxygen content 7,7 mg/l, after Microbubble Generator (MBG) on the run in the 1 hour in which it is dissolved oxygen content increased to 8,8 mg/l, the lowest oxygen content produced 8,0 mg/l and highest oxygen content produced 9,0 mg/lPenelitian  ini bertujuan untuk menerapkan jenis aerasi kolam ikan disebut Microbubble Generator  (MBG) untuk budidaya ikan. Microbubble Generator (MBG) dijalankan berdasarkan prinsip tabung venturi di mana air beredar melalui saluran menyempit  sehingga udara yang tersedot ke dalam perangkat  dan didorong oleh air yang mengalir untuk membuat gelembung  berukuran  mikro. Microbubble Generator (MBG) diuji Di Balai Riset Pemuliaan Ikan Subang (BRPI), Hasil menyoroti  potensi menjanjikan Microbubble Generator  (MBG) sebagai aerasi terjangkau  untuk diterapkan  dalam budidaya. Meskipun tingkat oksigen terlarut tidak berbeda secara signifikan dengan aerasi konvensional, Microbubble Generator (MBG) menunjukkan degradasi  lebih cepat dari kandungan  organik dalam air dan diinduksi pertumbuhan yang lebih cepat. Nozzel Venturi ini dibuat dengan bentuk yang berbeda antara input dan output. Lubang input nozzel venturi berbentuk setengah lingkaran yang berdiameter 18 mm di hulu dan keluaran berdiameter 3 mm, sedangkan untuk lubang output berbentuk kerucut yang berdiameter 8 mm di hulu dan keluaran berdiameter 14 mm dan untuk proses mengalirkan air menggunakan pompa semijet. Hasil dari pengujian microbubble generator (MBG) dimana kondisi awal kadar oksigen 7,7 mg/l, setelah microbubble generator (MBG) dijalankan dalam waktu 1 jam kadar oksigen yang terlarut meningkat menjadi 8,8 mg/l, kadar oksigen terendah yang dihasilkan 8,0 mg/l dan kadar oksigen tertinggi yang dihasilkan 9,0 mg/l.